Cinobufacini Injection Inhibits the Proliferation of Triple-Negative Breast Cancer Through the Pin1–TAZ Signaling Pathway - Kong, Lu; Liu, Xu; Yu, Bing; Yuan, Ye; Zhao, Qianru; Chen, Yuru; Qu, Bin; Du, Xue; Tian, Xiaoxuan; Shao, Rui; Wang, Yu (Frontiers in Pharmacology, 2022)
Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer (BC), which is characterized by the total absence of human epidermal growth factor receptor 2 (HER2), progesterone receptor (PR) and estrogen receptor (ER) expression. Cinobufacini injection (CI) is the aqueous extract from the dry skin of Bufo gargarizans, which is broadly used for the malignant tumors treatment. However, the potential mechanism of CI against TNBC, has not been fully revealed. In this study, we found that CI inhibited the proliferation of MDA-MB-231 and 4T1 cells in a time and dose dependent manner. RNA-seq data showed that down-regulatedand up-regulated genes were mainly enriched in biological processes related to tumor cell proliferation, including cell cycle arrest and regulation of apoptosis signaling pathways. Indeed, after CI treatment, the protein level of CDK1 and Bcl-2/Bax decreased, indicating that CI induced cell cycle of MDA-MB-231 arrest in G2/M phase and increased the rate of apoptosis. Meanwhile, CI significantly inhibited the growth of tumor in vivo, and RNA-seq data showed that TAZ signaling pathway played a vital role after CI treatment. Both immunohistochemistry and Western blot analysis confirmed the downregulation of Pin1 and TAZ, caused by CI treatment. Furthermore, the bioinformatics analysis indicated that Pin1 and TAZ were indeed elevated in TNBC patients, with poor staging, classification, and patient survival rate. In conclusion, CI effectively inhibited the proliferation of TNBC in vitro and in vivo and induced their apoptosis and cycle arrest through the Pin1-TAZ pathway.